THE EFFECT OF MUDHARABAH AND MUSYARAKAH FINANCING ON RETURN ON EQUITY IN SYARIAH BANKS IN INDONESIA - Isra Hayati; Silvi Rahmayani Hasibuan (Proceeding International Seminar of Islamic Studies, 2021)
The analytical method used in this research is descriptive statistical analysis, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test and multiple linear regression method using SPSS version 22. The linear regression results are Y = 3.505 - 0.092X1 + 0.819X2. From the t test of the mudharabah financing variable, it produces tcount -0.356 ttable 2.0047 and a significance value of 0.732 0.05. Then Ho is accepted and H1 is rejected, meaning that there is no influence of the mudharabah financing variable (X1) on the return on equity (Y) variable.Musyarakah financing resulted in tcount 3.179 ttable 2.0047 and a significance value of 0.002 0.05. So Ho is rejected and H2 is accepted, meaning that there is a significant positive influence on the variable of musyarakah financing (X2) on the return on equity (Y).F test obtained Fcount 143.348 Ftable 3.16 and a significance value of 0.000 0.05. This proves that Ho3 is rejected and H3 is accepted, meaning that there is a significant effect of mudharabah financing (X1) and musyarakah financing (X2) on return on equity (Y).Mudharabah Financing, Musharaka Financing and Return On Equity